Development of Fast-dissolving Oral Dosage Form as Tablet using Binder as Vigna Mungo Mucilage and Oral Film using Solvent Casting Technique: Comparative Study (Asian Journal of Pharmaceutics (AJP), 2023)
forms are the most preferred oral dosage forms as tablets and novel drug delivery as oral films. Sumatriptansuccinate is a new generation anti-migraine agent; Oral bioavailability of sumatriptan succinate is low due toits severe first-pass metabolism. Materials and Methods: An attempt was made to develop fast-dissolving anddisintegrating oral tablet and oral film for the sumatriptansuccinate to avoid first-pass metabolism. To developa fast-dissolving tablet a natural mucilage powder extracted from vigna mungo. The tablet formulations wereprepared using 2, 4, and 6% mucilage solution as a binder. Similarly, the oral films containing polyvinyl alcohol:soluplus or hydroxypropyl methyl cellulose: Soluplus were prepared by solvent casting method. The differentialscanning calorimetry and fourier transform infrared spectroscopy was carried out for plain drugs, blend of drugswith mucilage, formed granules andoral film. The developed oral fast-dissolving tablet and oral fast-dissolvingfilm formulations were evaluated for drug content, In vitro dissolution study. Results and Discussion: Tabletsformulated with 2% mucilage (B1) binder require less disintegration time and 100% drug dissolution within10 min. Film formulations containing HPMC K100M with soluplus containing 100 mg and 675 mg, respectively,resulted disintegration within 25 seconds and 96% of drug dissolution within 5 min. Conclusion: Hence, the fastdissolvingdosage form was successfully developed as film formulation as compared to tablets for the sumatriptansuccinate.